Illustrated seamanship - Dedekam, Ivar (Fernhurst Books Limited, 2007)
Today, yachts are often equipped with electrical windlasses, autopilot, bow thrusters, etc. This equipment has also become much more reliable, making it possible to make long offshore passages without much knowledge of seamanship. However, as the coastguards in many countries can confirm, more and more yachts require assistance, even when they should be able to reach harbour on their own. In this book you will be shown the traditional techniques you should be familiar with - regarding rope handling, manoeuvring and anchoring - in order to make long or short passages safely. Each element is clearly explained alongside detailed illustrations, combining to make a straightforward and easy-to-follow guide. Although yacht gear is becoming more and more reliable, you can be almost sure that, sooner or later, it will fail or you will be out of electrical power to use it. Learning the traditional techniques may not only be necessary but is also both interesting and fun. Instead of waking up the entire harbour in the early hours with the noise of your bow thruster, you may, alternatively, use a spring line to get safely moored to or leave the pontoon quietly.